Peran Lembaga Pemasyarakatan Dalam Memenuhi Hak Kesehatan Narapidana Lanjut Usia - Subroto, Mitro; Iswar, Iswar (Jurnal Ilmiah Wahana Pendidikan, 2025)
The shift in Indonesia’s criminal justice system towards corrections highlights a more humane approach, prioritizing the protection of inmates' rights. Law No. 22 of 2022 on Corrections ensures the fulfillment of basic rights, including healthcare and nutrition for inmates, with particular attention to vulnerable groups such as the elderly. Elderly inmates, defined as those aged 60 and above, face greater health risks due to aging, requiring specialized care and attention. However, the healthcare services provided to them in correctional facilities remain inadequate, with insufficient medical personnel, limited geriatric care, and a lack of proper nutrition tailored to their needs. This study employs a descriptive qualitative approach to analyze the role of correctional institutions in meeting the healthcare rights of elderly inmates. It identifies key challenges such as the lack of medical resources, inadequate living conditions, and unmet daily needs. To address these issues, the study suggests improving cooperation with external health agencies, enhancing medical facilities, and standardizing the provision of essential supplies to ensure the well-being of elderly inmates in correctional settings.